Skip to main content
Mathematics LibreTexts

7.1e: Verifying Trigonometric Identities

  • Page ID
    73015
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)\(\newcommand{\AA}{\unicode[.8,0]{x212B}}\)

    A: Simplify

    Exercise \(\PageIndex{A}  \)

    \( \bigstar \\[4pt] \) Simplify each of the following to an expression involving a single trig function with no fractions.

    1. \(\csc (t)\tan \left(t\right) \\[1pt] \)

    2. \(\cos (t)\csc \left(t\right) \\[1pt] \)

    3. \(\sin x \cos x \sec x\\[1pt] \)

    4. \(\tan x\sin x+\sec x\cos^2x\\[1pt] \)

    5. \(\sin(-x)\cos(-x)\csc(-x)\\[1pt] \)

    6. \(\csc x+\cos x\cot(-x)\\[1pt] \)

    7. \(-\tan(-x)\cot(-x)\\[1pt] \)

    8. \(3\sin^3 t\csc t+\cos^2 t+2\cos(-t)\cos t\\[1pt] \)

    9. \(\dfrac{\sec \left(t\right)}{\csc \left(t\right)\; } \\[4pt] \)

    10. \(\dfrac{\cot \left(t\right)}{\csc \left(t\right)} \\[4pt] \)

    11. \(\dfrac{\sec \left(t\right)-\cos \left(t\right)}{\sin \left(t\right)} \\[4pt] \)

    12. \(\dfrac{\cot t+\tan t}{\sec (-t)}\\[4pt] \)

    13. \(\dfrac{-\sin (-x)\cos x\sec x\csc x\tan x}{\cot x}\\[4pt] \)

    14. \(\dfrac{\sin ^{2} \left(t\right)+\cos ^{2} \left(t\right)}{\cos ^{2} \left(t\right)} \\[4pt] \)

    15. \(\dfrac{1-\sin ^{2} \left(t\right)}{\sin ^{2} \left(t\right)} \\[4pt] \)

    16. \(\dfrac{1-\cos ^2 x}{\tan ^2 x}+2\sin ^2 x\\[4pt] \)

    17. \(\dfrac{1+\tan ^2\theta }{\csc ^2\theta }+\sin ^2\theta +\dfrac{1}{\sec ^2 \theta }\\[4pt] \)

    18. \(\dfrac{\tan \left(t\right)}{\sec \left(t\right)-\cos \left(t\right)} \\[4pt] \)

    19. \(\dfrac{1+\cot \left(t\right)}{1+\tan \left(t\right)} \\[4pt] \)

    20. \(\dfrac{1+\sin \left(t\right)}{1+\csc \left(t\right)} \\[4pt] \)

    21. \(\left (\dfrac{\tan x}{\csc ^2 x}+\dfrac{\tan x}{\sec ^2 x} \right )\left (\dfrac{1+\tan x}{1+\cot x} \right )-\dfrac{1}{\cos ^2 x}\\[4pt] \)

    Answers to odd exercises.

    1. \(  \sec (t) \)     3. \(\sin x  \)     5. \(\cos x\  \)    7. \(-1  \)     9. tan(\(t   \))     11. tan(\(t  \))     
    13. \( \tan^2 (x) \)      15. \( \cot^2 (t)  \)     17. \(\sec^2 (x)  \)     19. cot(\(t   \))     21. \( -1 \)

    \( \bigstar \) Simplify the first trigonometric expression into an expression that is exclusively a function of the second expression.

    24. \(\tan x\);  \(f( \sec x) \\[4pt] \)

    25. \(\sec x\);  \(f( \cot x) \\[4pt] \)

    26. \(\sec x\);  \(f( \sin x) \\[4pt] \)

    27. \(\cot x\);  \(f( \sin x) \\[4pt] \)

    28. \(\cot x\);  \(f( \csc x) \\[4pt] \)

    29. \((\sec x+\csc x)(\sin x+\cos x)-2-\cot x\);  \(f( \tan x) \\[4pt] \)

    30. \(\dfrac{\tan x+\cot x}{\csc x}\);  \(f( \cos x)  \\[4pt] \)

    31. \(\dfrac{\sec x+\csc x}{1+\tan x}\);  \(f( \sin x) \\[4pt] \)

    32. \(\dfrac{1}{\csc x-\sin x}\);  \(f( \sec x, \; \tan x) \\[4pt] \)

    33. \(\dfrac{1}{\sin x\cos x}-\cot x\);  \(f( \cot x) \\[4pt] \)

    34. \(\dfrac{\cos x}{1+\sin x}+\tan x\);  \(f( \cos x) \\[4pt] \)

    35. \(\dfrac{1-\sin x}{1+\sin x}-\dfrac{1+\sin x}{1-\sin x}\);  \(f( \sec x, \; \tan x) \\[4pt] \)

    36. \(\dfrac{1}{1-\cos x}-\dfrac{\cos x}{1+\cos x}\);  \(f( \csc x) \\[4pt] \)

    Answers to odd exercises.

    25. \( \pm  \sec  x  \)     27. \( \pm  \cot  x \)     29. \(\tan x  \)     31. \(\dfrac{1}{\sin x}  \)     33. \(\dfrac{1}{\cot x}  \)     35. \(-4\sec x \tan x  \)

    B: Verify (no fractions)

    Exercise \(\PageIndex{B}\)

    \( \bigstar \) Verify the following identities.

    41. \(\cos \theta   \tan \theta  =~ \sin\;\theta\\[4pt] \)

    42. \(\sin\;\theta ~ \cot\;\theta ~=~ \cos\;\theta\\[4pt] \)

    43. \(\text{sec}(a) - \text{cos}(a) = \text{sin}(a) \text{tan}(a) \\[4pt] \)

    44. \(\cos x-\cos^3x=\cos x \sin^2 x\\[4pt] \)

    45. \(\tan ^{2} \theta \csc ^{2} \theta-\tan ^{2} \theta = 1\\[4pt] \)

    46. \( \sin ^{2} \theta \cot ^{2} \theta+\sin ^{2} \theta = 1\\[4pt] \)

    47. \(3\sin^2 \theta + 4\cos^2 \theta =3+\cos^2\theta\\[4pt] \)

    48. \(\sin^4 \;\theta ~-~ \cos^4 \;\theta ~=~ \sin^2 \;\theta ~-~ \cos^2 \;\theta\\[4pt] \)

    49. \(\cos^2x-\tan^2x=2-\sin^2x-\sec^2x\\[4pt] \)

    50. \(\cos^4 \;\theta ~-~ \sin^4 \;\theta ~=~ 1 ~-~ 2\;\sin^2 \;\theta\\[4pt] \)

    51. \(\sec ^{4} \theta-\sec ^{2} \theta = \tan ^{4} \theta+\tan ^{2} \theta\\[4pt] \)

    52. \(\csc ^{4} \theta-\csc ^{2} \theta = \cot ^{4} \theta+\cot ^{2} \theta \)

    53. \(\cos \theta(\sec \theta-\cos \theta) = \sin ^{2} \theta\\[4pt] \)

    54. \(\tan \theta(\cot \theta+\tan \theta) = \sec ^{2} \theta\\[4pt] \)

    55. \(\tan \theta(\csc \theta+\cot \theta)-\sec \theta = 1\\[4pt] \)

    56. \(\cot \theta(\sec \theta+\tan \theta)-\csc \theta = 1\\[4pt] \)

    57. \(\cos \theta(\tan \theta+\cot \theta) = \csc \theta\\[4pt] \)

    58. \(\sin \theta(\cot \theta+\tan \theta) = \sec \theta\\[4pt] \)

    59. \(1 + \text{cot} (x) = \text{cos} (x) (\text{sec}(x) + \text{csc} (x)) \\[4pt] \)

    60. \(\cos x(\tan x-\sec(-x))=\sin x-1\\[4pt] \)

    61. \(\csc^2x(1-\sin^2x)=\cot^2x\\[4pt] \)

    62. \( ( \sin \theta+\cos \theta)^{2}+(\sin \theta-\cos \theta)^{2} = 2\\[4pt] \)

    63. \((\sin x+\cos x)^2=1+2 \sin x\cos x \)

    Answers to odd exercises.
    41. \( \cos \theta   \tan \theta  =  \dfrac{\cos \theta}{1} \cdot   \dfrac{\sin \theta}{\cos \theta} =\sin \theta \)
    43. \( \cos x-\cos^3x = \cos x (1-\cos^2 x) = \cos x\sin ^x   \)
    45.  \( \tan ^{2} \theta \csc ^{2} \theta-\tan ^{2} \theta \) =  \( \dfrac{\sin^2 \theta}{\cos^2 \theta} \cdot \dfrac{1}{\sin^2 \theta} - \dfrac{\sin^2 \theta}{\cos^2 \theta} \) =  \(  \dfrac{1-\sin^2 \theta}{\cos^2 \theta} \) =  \(  \dfrac{\cos^2 \theta}{\cos^2 \theta} \) =  \(  1 \)
    47. \(  3\sin^2\theta + 4\cos^2\theta  = 3\sin ^2\theta +3\cos ^2\theta +\cos^2\theta  = 3\left ( \sin ^2\theta +\cos ^2\theta \right )+\cos^2\theta  = 3+\cos^2\theta \)
    49. \(  \cos^2x-\tan^2x  = 1-\sin^2x-\left (\sec^2x -1 \right ) = 1-\sin^2x-\sec^2x +1 = 2-\sin^2x-\sec^2x   \)
    51. \(\sec ^{4} \theta-\sec ^{2} \theta = \sec ^{2} \theta ( \sec ^{2} \theta-1) = (1+\tan^2 \theta ) (1+\tan^2 \theta  -1) = (1+\tan^2 \theta ) \tan^2 \theta  = \tan ^{4} \theta+\tan ^{2} \theta \)

    53. \( \cos \theta(\sec \theta-\cos \theta) = \cos \theta \sec \theta-\cos^2 \theta = 1-  \cos^2 \theta  = \sin ^{2} \theta  \)
    55. \(\tan \theta(\csc \theta+\cot \theta)-\sec \theta = \dfrac{\sin \theta}{\cos \theta} \cdot  \dfrac{1}{\sin \theta} + \dfrac{\sin \theta}{\cos \theta} \cdot  \dfrac{\cos \theta }{\sin \theta} - \dfrac{1}{\cos \theta}=  \dfrac{1}{\cos \theta} + 1 - \dfrac{1}{\cos \theta} = 1  \)
    57. \(\cos \theta(\tan \theta+\cot \theta) = \dfrac{\cos \theta}{1} \cdot \dfrac{\sin \theta}{\cos \theta}+ \dfrac{\cos \theta}{1}  \cdot  \dfrac{\cos \theta }{\sin \theta} = \dfrac{ \sin^2 \theta}{\sin \theta} +\dfrac{ \cos^2 \theta}{\sin \theta}  =\dfrac{\sin^2 \theta+ \cos^2 \theta}{\sin \theta} = \dfrac{1}{\sin \theta} = \csc \theta  \)
    59. \(  \text{cos} (x) (\text{sec}(x) + \text{csc} (x))  = \dfrac{cos \theta}{1} \cdot \dfrac{1}{cos \theta}+\dfrac{cos \theta}{1} \cdot  \dfrac{1}{\sin \theta} =1 + \cot \theta \)
    61. \(\csc^2x(1-\sin^2x) =\csc^2x - 1 =\cot^2x + 1  - 1 = \cot^2 x  \)
    63. \((\sin x+\cos x)^2 = \sin^2 + 2 \sin x \cos x + \cos^2 x =1+2 \sin x\cos x  \)

     

    C: Verify (fractions)

    Exercise \(\PageIndex{C}\)

    \( \bigstar \) Verify the following identities.

    71. \(\dfrac{\tan\;\theta}{\cot\;\theta} ~=~ \tan^2 \;\theta\\[4pt] \)

    72. \(\dfrac{\csc\;\theta}{\sin\;\theta} ~=~ \csc^2 \;\theta\\[4pt] \)

    73. \(\dfrac{\tan x}{\sec x}\sin (-x)=\cos ^2 x -1\\[4pt] \)

    74. \(\dfrac{1 ~-~ 2\;\cos^2 \;\theta}{\sin\;\theta ~ \cos\;\theta} ~=~ \tan\;\theta ~-~ \cot\;\theta\  \)

    75. \(\dfrac{1+\sin ^2x}{\cos ^2 x}=1+2\tan ^2x\\[4pt] \)

    76. \(\dfrac{1 + \text{tan}^2(b)}{\text{tan}^2(b)} = \text{csc}^2(b) \)

    77. \(\dfrac{\cos \theta}{\tan \theta}-\csc \theta = -\sin \theta\\[4pt] \)

    78. \(\dfrac{\sin \theta}{\cot \theta}-\sec \theta = -\cos \theta \\[4pt]  \)

    79. \(\text{tan}^{2} (t) = \dfrac{1}{\text{cos}^2(t)} - 1 \\[4pt] \)

    80. \(\dfrac{(\sin \theta+\cos \theta)^{2}}{\cos \theta}-\sec \theta=2 \sin \theta\\[4pt] \)

    81. \(\dfrac{(1 + \text{cos} A)(1 - \text{cos} A)}{\text{sin} A} = \text{sin} A  \)

    Answers to odd exercises.
    71. \(\dfrac{\tan \theta}{\cot \theta} = \tan \theta  \cdot \dfrac{1}{\cot \theta} = \tan \theta  \cdot  \tan \theta = \tan^2  \theta  \)
    73. \(  \dfrac{\tan x}{\sec x}\sin (-x) =\dfrac{\sin x}{\cos x} \cdot \dfrac{\cos x}{1} \cdot \sin x = -sin^2 x = - (1- \cos^2 x)   =\cos ^2 x -1  \)
    75. \(  \dfrac{1+\sin ^2 x}{\cos ^2 x} = \dfrac{1}{\cos ^2 x}+\dfrac{\sin ^2x}{\cos ^2 x} = \sec ^2x+\tan ^2x = \tan ^2x+1+\tan ^2x = 1+2\tan ^2x \)
    77. \(\dfrac{\cos \theta}{\tan \theta}-\csc \theta =  \dfrac{\cos \theta}{1}  \cdot  \dfrac{\cos \theta}{\sin \theta} - \dfrac{1}{\sin \theta}   =  \dfrac{\cos^2  \theta - 1}{\sin \theta}  = \dfrac{\sin^2 \theta}{\sin \theta} = -\sin \theta \)
    79. \(\text{tan}^{2} (t) = \dfrac{1}{\text{cos}^2(t)} - 1  = \dfrac{ 1}{ \cos^2 t} - \dfrac{ \cos^2 t}{ \cos^2 t} = \dfrac{ \cos^2 t - 1}{ \cos^2 t} = \dfrac{ -(1-\cos^2 t)}{ \cos^2 t} =\dfrac{ \sin^2 t }{ \cos^2 t} = \tan^2 t  \)
    81. \(\dfrac{(1 + \text{cos}(A))(1 - \text{cos} (A))}{\text{sin} (A)} = \dfrac{1 - \cos^2 (A))}{\sin (A)} = \dfrac{ \sin^2 (A))}{\sin (A)} = \sin (A)  \)

    \( \bigstar \) Verify the following identities.

    82. \(\dfrac{\csc \theta}{\cos \theta}-\dfrac{\cos \theta}{\csc \theta} = \dfrac{\cot ^{2} \theta+\sin ^{2} \theta}{\cot \theta}\\[4pt] \) 

    83. \(\dfrac{\sec \theta}{\csc \theta} + \dfrac{\sin \theta}{\cos \theta} = 2 \tan \theta\\[4pt] \)

    84. \(\dfrac{\text{csc}^2 (\alpha) - 1}{\text{csc}^2 (\alpha) - \text{csc} (\alpha)} = 1 + \text{sin} (\alpha) \\[4pt] \)

    85. \(\dfrac{\sin \theta \tan \theta+\sin \theta}{\tan \theta+\tan ^{2} \theta} = \cos \theta\\[4pt] \)

    86. \(\dfrac{\cos \theta \cot \theta+\cos \theta}{\cot \theta+\cot ^{2} \theta} = \sin \theta\\[4pt] \)

    87. \(\dfrac{\sin^2 \;\theta}{1 ~-~ \sin^2 \;\theta} ~=~ \tan^2 \;\theta\\[4pt] \)

    88. \(\dfrac{1 ~-~ \tan^2 \;\theta}{1 ~-~ \cot^2 \;\theta} ~=~ 1 ~-~ \sec^2 \;\theta\\[4pt] \)

    89. \(\dfrac{\sec ^{2} \theta}{1+\cot ^{2} \theta} = \tan ^{2} \theta\\[4pt] \)

    90. \(\dfrac{\cos ^2 \theta -\sin ^2 \theta }{1-\tan ^2 \theta }= 1 - \sin ^2 \theta\\[4pt] \)

    91. \(\dfrac{\csc ^{2} \theta}{1+\tan ^{2} \theta} = \cot ^{2} \theta\\[4pt] \)

    92. \(\sin\;\theta ~=~ \pm\,\dfrac{\tan\;\theta}{\sqrt{1 ~+~
    \tan^2 \;\theta}}\qquad \\[4pt] \)

    93. \(\dfrac{\sec \theta +\tan \theta }{\sin \theta(\cot \theta+\cos \theta) }=\sec ^2 \theta\\[4pt] \)

    Answers to odd exercises.
    83. \( \dfrac{\sec \theta}{\csc \theta} + \dfrac{\sin \theta}{\cos \theta} = \dfrac{\sec \theta}{1} \cdot \dfrac{1}{\csc \theta} + \dfrac{\sin \theta}{\cos \theta} =\dfrac{1}{\cos  \theta}\cdot \dfrac{\sin \theta}{1} + \dfrac{\sin \theta}{\cos \theta} = 2 \dfrac{\sin \theta}{\cos \theta}= 2 \tan \theta \\[2pt] \)
    85. \(\dfrac{\sin \theta \tan \theta+\sin \theta}{\tan \theta+\tan ^{2} \theta} = \dfrac{\sin \theta ( \tan \theta+1)}{\tan \theta(1 + \tan \theta) } = \sin \theta \cdot \cot \theta =\sin \theta \cdot \dfrac{\cos \theta}{\sin \theta} = \cos \theta  \)
    87. \(\dfrac{\sin^2 \;\theta}{1 ~-~ \sin^2 \;\theta} = \dfrac{\sin^2 \theta}{ \cos^2 \theta} = \left(  \dfrac{\sin \theta}{\cos \theta}  \right)^2  = \tan^2 \;\theta  \)
    89. \(\dfrac{\sec ^{2} \theta}{1+\cot ^{2} \theta} = \dfrac{\sec ^{2} \theta}{\csc ^{2} \theta} = \dfrac{1}{\cos^2 \theta} \cdot \dfrac{\sin^2 \theta}{1}   =  \tan ^{2} \theta  \)
    91. \(\dfrac{\csc ^{2} \theta}{1+\tan ^{2} \theta} =  \dfrac{\csc ^{2} \theta}{\sec ^{2} \theta} = \dfrac{1}{\sin^2 \theta} \cdot \dfrac{\cos^2 \theta}{1}    = \cot ^{2} \theta  \) 
    93. \( \dfrac{\sec \theta +\tan \theta }{\sin \theta(\cot \theta+\cos \theta) } = \dfrac{    \dfrac{1}{\cos \theta} +  \dfrac{\sin \theta}{\cos \theta}   }{\sin \theta \left(  \dfrac{\cos \theta}{\sin \theta} +\cos \theta  \right) } = \dfrac{    \dfrac{1}{\cos \theta} (1+  \sin \theta)   }{\cos \theta \sin \theta \left(  \dfrac{1}{\sin \theta} + 1 \right) } = \dfrac{    \dfrac{1}{\cos \theta} (1+  \sin \theta)   }{\cos \theta \left(  1 + \sin \theta \right) }   =\dfrac{1}{\cos^2 \theta} = \sec ^2 \theta  \)

    D: Verify (more fractions)

    Exercise \(\PageIndex{D}\)

    \( \bigstar \) Verify the following identities.

    101. \(\dfrac{1+\sin x}{\cos x}=\dfrac{\cos x}{1+\sin (-x)}\\[4pt] \)

    102. \(\dfrac{\cos^2 \;\theta}{1 ~+~ \sin\;\theta} ~=~ 1 ~-~ \sin\;\theta\\[4pt] \)

    103. \(\dfrac{1 + \text{cos} (u)}{\text{sin} (u)} = \dfrac{\text{sin} (u)}{1 - \text{cos}(u)} \\[4pt] \)

    104. \(\dfrac{\sin ^{2} \left(\theta \right)}{1+\cos \left(\theta \right)} =1-\cos \left(\theta \right) \\[4pt] \)

    105. \(\dfrac{1 ~-~ \tan\;\theta}{1 ~+~ \tan\;\theta} ~=~ \dfrac{\cot\;\theta ~-~ 1}{\cot\;\theta ~+~ 1}\\[4pt] \)

    106. \(\dfrac{\text{sin}^4 (\gamma) - \text{cos}^4 (\gamma)}{\text{sin} (\gamma) - \text{cos} (\gamma)} = \text{sin} (\gamma) + \text{cos} (\gamma) \\[4pt] \)

    107. \(\dfrac{\text{csc}^2 (x) - \text{sin}^2 (x)}{\text{csc} (x) + \text{sin} (x)} = \text{cos} (x) \text{cot} (x) \\[4pt] \)  

    108. \(\dfrac{\sec \theta-\cos \theta}{\sec \theta+\cos \theta} = \dfrac{\sin ^{2} \theta}{1+\cos ^{2} \theta}\\[4pt] \)

    109. \(\dfrac{\sec \theta+\tan \theta}{\cot \theta+\cos \theta} = \tan \theta \sec \theta\\[4pt] \)

    110. \(\dfrac{\tan\;\theta ~+~ \tan\;\phi}{\cot\;\theta ~+~ \cot\;\phi} ~=~
    \tan\;\theta ~ \tan\;\phi\\[4pt] \)

    111. \(\dfrac{\sec (-x)}{\tan x+\cot x}=-\sin (-x)\\[4pt] \)

    112. \(\dfrac{\sec \theta+\csc \theta}{\tan \theta+\cot \theta} = \sin \theta+\cos \theta\\[4pt] \) 

    113. \(\dfrac{\tan \theta-\cot \theta}{\tan \theta+\cot \theta} = \sin ^{2} \theta-\cos ^{2} \theta\\[4pt] \)

    114. \(\dfrac{\text{sin} (\theta) - \text{cos} (\theta)}{\text{sec}(\theta) - \text{csc} (\theta)} = \text{sin} (\theta) \text{cos} (\theta) \\[4pt] \)

    Answers to odd exercises.

    101. \(=\dfrac{\cos x}{1-\sin (x)} \times \dfrac{1+ \sin x}{1+ \sin x} = \dfrac{\cos x (1 + \sin x)}{1-\sin^2 x} = \dfrac{\cos x (1 + \sin x)}{\cos^2 x} = \dfrac{1+\sin x}{\cos x}  \)
    103. \(\dfrac{1 + \text{cos} (u)}{\text{sin} (u)} =  \dfrac{1 + \text{cos} (u)}{\text{sin} (u)} \cdot \dfrac{\sin u}{\sin u} =  \dfrac{\sin u (1 + \cos u) }{\sin^2 u} =  \dfrac{\sin u (1 + \cos u) }{1-\cos^2 u} =  \dfrac{\sin u (1 + \cos u) }{(1-\cos u)(1+\cos u)} \\ \)
    \( \quad =  \dfrac{\text{sin} (u)}{1 - \text{cos}(u)} \)
    105. \(\dfrac{1 ~-~ \tan\;\theta}{1 ~+~ \tan\;\theta} =  \dfrac{(1 ~-~ \tan\;\theta)}{(1 ~+~ \tan\;\theta)}  \cdot \dfrac{\cot  \theta}{\cot \theta}  =   \dfrac{\cot\;\theta ~-~ 1}{\cot\;\theta ~+~ 1} \)
    107. \(\dfrac{\text{csc}^2 (x) - \text{sin}^2 (x)}{\text{csc} (x) + \text{sin} (x)} =  \dfrac{( \csc x - \sin x)(\csc x + \sin x)}{(\csc x + \sin x)}\ = \csc x - \sin x = \dfrac{1}{\sin x} -  \dfrac{\sin^2 x}{\sin x} = \dfrac{1 - \sin^2 x}{\sin x} \\ \)
    \( \quad  = \dfrac{ \cos^2 x}{\sin x} = \cos x \cdot \dfrac{\cos x}{ \sin x} = \text{cos} (x) \text{cot} (x) \ \)

    109. \(\dfrac{\sec \theta+\tan \theta}{\cot \theta+\cos \theta} =  \dfrac{\dfrac{1}{\cos \theta}+\dfrac{\sin \theta}{\cos \theta}}{\dfrac{\cos \theta}{\sin \theta}+\dfrac{\cos \theta \sin \theta}{\sin \theta}} =  \dfrac{\dfrac{1+\sin \theta}{\cos \theta}}{\dfrac{\cos \theta \left( 1+ \sin \theta \right)}{\sin \theta} } =  \dfrac{1+\sin \theta}{\cos \theta} \cdot \dfrac{\sin \theta}{\cos \theta \left( 1+ \sin \theta \right)} = \dfrac{\sin \theta }{\cos^2 \theta } \\ \)
    \( \quad  = \dfrac{\sin \theta }{\cos \theta } \cdot \dfrac{1}{\cos \theta}= \tan \theta \sec \theta \)
    111. \(\dfrac{\sec (-x)}{\tan x+\cot x} =  \dfrac{\sec (x)}{\dfrac{\sin x}{\cos x}+\dfrac{\cos x}{\sin x}} =  \dfrac{\dfrac{1}{\cos x}}{\dfrac{\sin^2 x + \cos^2 x}{\cos x \sin x}} =  \dfrac{\dfrac{1}{\cos x}}{\dfrac{1}{\cos x \sin x}} =\dfrac{1}{\cos x} \cdot \dfrac{\cos x \sin x}{1}  = \sin x  =  -\sin (-x)\\[4pt] \)
    113. \(\dfrac{\tan \theta-\cot \theta}{\tan \theta+\cot \theta} = \dfrac{\dfrac{\sin \theta}{\cos \theta}-\dfrac{\cos \theta}{\sin \theta}}{\dfrac{\sin \theta}{\cos \theta}+\dfrac{\cos \theta}{\sin \theta}} =\dfrac{\dfrac{\sin^2 \theta - \cos^2 \theta}{\sin \theta\cos \theta}}{\dfrac{\sin^2 \theta + \cos^2 \theta}{\sin \theta\cos \theta}}= \dfrac{\dfrac{\sin^2 \theta - \cos^2 \theta}{\sin \theta\cos \theta}}{\dfrac{1}{\sin \theta\cos \theta}} = \dfrac{\sin^2 \theta - \cos^2 \theta}{\sin \theta\cos \theta} \cdot \dfrac{\sin \theta\cos \theta}{1} \\ \)
    \( \quad  =  \sin ^{2} \theta-\cos ^{2} \theta \)

     \( \bigstar \) Verify the following identities.

    115. \(\dfrac{\sin \theta}{1+\sin \theta}-\dfrac{\sin \theta}{1-\sin \theta} = -2 \tan ^{2} \theta\\[4pt] \)

    116. \(\dfrac{\cos \theta}{1+\cos \theta}-\dfrac{\cos \theta}{1-\cos \theta} = -2 \cot ^{2} \theta\\[4pt] \)

    117. \(\dfrac{1}{1+\cos x}-\dfrac{1}{1-\cos (-x)}=-2\cot x\csc x\\[4pt] \)

    118. \(\dfrac{\cot \theta}{1-\csc \theta}-\dfrac{\cot \theta}{1+\csc \theta} = 2 \sec \theta\\[4pt] \) 

    119. \(\dfrac{\tan \theta}{1+\sec \theta}-\dfrac{\tan \theta}{1-\sec \theta} = 2 \csc \theta\\[4pt] \)

    120. \(\dfrac{1-\sin \theta}{\cos \theta}+\dfrac{\cos \theta}{1-\sin \theta} = 2 \sec \theta\\[4pt] \)

    121. \(\dfrac{\cos \theta}{1+\sin \theta}+\dfrac{1+\sin \theta}{\cos \theta} = 2 \sec \theta\\[4pt] \)

    122. \(1-\dfrac{\cos ^{2} \theta}{1+\sin \theta} = \sin \theta\\[4pt] \)

    123. \(1-\dfrac{\sin ^{2} \theta}{1+\cos \theta} = \cos \theta\\[4pt] \)

    124. \(2 \text{sec}^2 (t) = \dfrac{1 - \text{sin}(t)}{\text{cos}^2 (t)} + \dfrac{1}{1 -  \text{sin} (t)} \\[4pt] \)

    125. \(\left (\dfrac{\sec ^2(-x)-\tan ^2x}{\tan x} \right )\left (\dfrac{2+2\tan x}{2+2\cot x} \right )-2\sin ^2x \\ \)      \( \qquad =\cos^2 x - \sin^2 x \\[4pt] \)

    Answers to odd exercises.
    115. \(\dfrac{\sin \theta}{1+\sin \theta}-\dfrac{\sin \theta}{1-\sin \theta} =  \dfrac{\sin \theta}{(1+\sin \theta)} \cdot \dfrac{(1-\sin \theta)}{(1-\sin \theta)} - \dfrac{\sin \theta}{(1-\sin \theta)} \cdot \dfrac{(1+\sin \theta)}{(1+\sin \theta)} \\ \)
    \( \qquad  = \dfrac{(\sin \theta -\sin^2 \theta) - (\sin \theta +\sin^2 \theta) }{1 - \sin^2 \theta} = \dfrac{-2 \sin^2 \theta}{\cos^2 \theta} =    -2 \tan ^{2} \theta \)
    117. \(\dfrac{1}{1+\cos x}-\dfrac{1}{1-\cos (-x)} =  \dfrac{1}{(1+\cos x)} \dfrac{(1 - \cos x)}{(1 - \cos x)}  -\dfrac{1}{(1-\cos x)}\dfrac{(1 + \cos x)}{(1 + \cos x)}  = \dfrac{(1 - \cos x) - (1 + \cos x)}{1-\cos^2 x} \\ \)
    \( \qquad  = \dfrac{ -2 \cos x }{ \sin^2 x} =   \dfrac{ -2 \cos x }{ \sin x} \cdot \dfrac{ 1}{ \sin x}  =-2\cot x\csc x \)
    119. \(\dfrac{\tan \theta}{1+\sec \theta}-\dfrac{\tan \theta}{1-\sec \theta} = \dfrac{\tan \theta}{(1+\sec \theta)}\dfrac{(1-\sec \theta)}{(1-\sec \theta)} -\dfrac{\tan \theta}{(1-\sec \theta)} \dfrac{(1+\sec \theta)}{(1+\sec \theta)} = \dfrac{-2 \tan \theta \sec \theta }{1-\sec^2 \theta } = \dfrac{-2 \tan \theta \sec \theta }{-\tan^2 \theta } \\ \)
    \( \qquad = \dfrac{2  \sec \theta }{\tan\theta } =   \dfrac{2  \sec \theta }{1 } \cdot \dfrac{\cos \theta }{\sin\theta } =\dfrac{2}{\sin\theta} =  2 \csc \theta \)
    121. \(\dfrac{\cos \theta}{1+\sin \theta}+\dfrac{1+\sin \theta}{\cos \theta} = \dfrac{\cos \theta}{(1+\sin \theta)}\dfrac{\cos \theta}{\cos \theta}+\dfrac{(1+\sin \theta)}{\cos \theta} \dfrac{(1+\sin \theta)}{(1+\sin \theta)} = \dfrac{\cos^2 \theta + 1 + 2 \sin \theta + \sin^2 \theta}{\cos \theta (1+\sin \theta)}  \\ \)
    \( \qquad  = \dfrac{2 + 2 \sin \theta }{\cos \theta (1+\sin \theta)} = \dfrac{2(1+ \sin \theta )}{\cos \theta (1+\sin \theta)}= \dfrac{2}{\cos \theta}  =  2 \sec \theta \)
    123. \(1-\dfrac{\sin ^{2} \theta}{1+\cos \theta} =1-\dfrac{1-\cos^{2} \theta}{1+\cos \theta} =1-\dfrac{(1-\cos \theta)(1+\cos \theta)}{1+\cos \theta} = 1 - (1-\cos \theta)=  \cos \theta \)
    125. \(\left (\dfrac{\sec ^2(-x)-\tan ^2x}{\tan x} \right )\left (\dfrac{2+2\tan x}{2+2\cot x} \right )-2\sin ^2x =  \left (\dfrac{1+\tan ^2x -\tan ^2x}{\tan x} \right )  \dfrac{2 \left( 1+    \dfrac{\sin x}{\cos x}     \right) }{  2 \left( 1+    \dfrac{\cos x}{\sin x}     \right)  } -2\sin ^2x \\ \)
    \( \qquad  =  \dfrac{1}{\tan x} \cdot  \dfrac{ \dfrac{\cos x +\sin x}{\cos x}}{\dfrac{\sin x+\cos x}{\sin x} }  - \sin^2 x=    \dfrac{\cos x}{\sin x} \cdot \dfrac{\cos x +\sin x}{\cos x} \cdot \dfrac{\sin x}{\sin x+\cos x}  -2\sin ^2x = 1 -2\sin ^2x \\ \)
    \( \qquad  = \cos^2 x + \sin^2 x  -2\sin ^2x = \cos^2 x - \sin^2 x \)

    \( \bigstar  \)

     


    7.1e: Verifying Trigonometric Identities is shared under a not declared license and was authored, remixed, and/or curated by LibreTexts.

    • Was this article helpful?